42.0k views
2 votes
Please solve with explanation

Please solve with explanation-example-1
User Hulufei
by
4.5k points

1 Answer

5 votes

Answer:

Rewrite the equation as 28a^4+ma^3−19a^2−2a+3=(7a^2+2a−3)(4a^2−1).

28a^4+ma^3−19a^2−2a+3=(7a^2+2a−3)(4a^2−1)

Simplify (7a^2+2a−3)(4a^2−1).

28a^4+ma^3−19a^2−2a+3=28a^4−19a^2+8a^3−2a+3

Move all terms not containing m to the right side of the equation.

ma^3=8a^3

Divide each term by a3 and simplify.

m=8

Explanation:

Hope to help you

User Russell Young
by
4.4k points